High-performance bio-based fluorine-free ski functional fabric and preparation method thereof
Patent Information
- Application Number
- CN202611359667.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-27
AI Technical Summary
然而研究表明,含氟化合物具有难降解性、生物累积性及潜在生理毒性,随着全球环保法规日趋严格,开发无氟防水体系已成为纺织功能面料领域的必然发展趋势
(1)本发明的铁磁基无氟超疏水涂料以多不饱和脂肪酸改性海绵铁粉搭配六方氮化硼构建微纳二元粗糙疏水结构,实现无氟超疏水效果,以PET/PDMS防水透湿功能膜为主体膜,将铁磁基无氟超疏水涂料以等间距弧形膜带的非全域涂覆方式,区别于传统全表面涂层,在通过疏水结构提升防水性的同时,最大程度保留了PET/PDMS纳米纤维膜的孔隙结构,有效解决了常规防水涂层易堵塞孔隙、透湿透气性大幅下降的技术矛盾,可高效排出运动水汽,提升穿着舒适性。
Smart Images

Figure REF-OBJ-1788421033824-000001 
Figure REF-OBJ-1788421033824-000005 
Figure REF-OBJ-1788421033824-000012
Abstract
Description
Technical Field
[0001] This invention relates to the field of fabric technology, specifically to a high-performance bio-based fluorine-free skiing functional fabric and its preparation method. Background Technology
[0002] Skiing places stringent demands on the comprehensive performance of functional fabrics: they need excellent waterproofing to prevent snowmelt penetration, good breathability to expel moisture generated during the activity, and high abrasion resistance and environmental friendliness. Traditional skiwear fabrics rely heavily on fluorinated waterproofing agents, with perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) being widely used due to their excellent hydrophobic and oleophobic properties. However, research indicates that fluorinated compounds are difficult to degrade, bioaccumulate, and have potential physiological toxicity. With increasingly stringent global environmental regulations, the development of fluorine-free waterproofing systems has become an inevitable trend in the field of functional textiles.
[0003] Existing fluorine-free waterproof technologies mainly include paraffin-based, siloxane-based, and nanoparticle coating methods, but they generally suffer from poor hydrophobic durability, insufficient water pressure resistance, and significant decrease in moisture permeability. Among these, electrospun nanofiber membranes, with their high porosity and three-dimensional network structure, have shown application potential in the field of waterproof and breathable functional fabrics. Electrospun membranes made from polymers such as polyethylene terephthalate and polydimethylsiloxane can achieve certain waterproof and breathable effects through structural control. However, pure nanofiber membranes have low mechanical strength and weak interlayer bonding after being laminated with fabrics. Under repeated bending and friction, the coating is prone to peeling and the membrane layer is easily damaged, making it difficult to adapt to the high-intensity use environment of skiing.
[0004] To improve the hydrophobic and mechanical properties of nanofiber membranes, existing technologies attempt to introduce inorganic particles to construct micro-nano binary rough structures. However, the particles exhibit poor dispersion uniformity, are prone to aggregation, and struggle to form a regular hydrophobic structure. Furthermore, most coatings employ a full-area coating method, which, while improving water pressure resistance, significantly clogs membrane pores, leading to a substantial decrease in moisture permeability and breathability, failing to achieve a balance between waterproofing and breathability. In addition, existing waterproof and breathable composite fabrics often use ordinary synthetic fiber fabrics as the base material, which have poor biodegradability and do not align with the green and low-carbon development trend. While bio-based nylon fabrics offer environmental advantages, their elasticity and waterproofness are limited, and when combined with functional membranes, their abrasion resistance and interlayer peel strength fail to meet the standards for skiwear.
[0005] This invention is proposed to meet the comprehensive performance requirements of high-end outdoor sports fabrics. Summary of the Invention
[0006] The purpose of this invention is to provide a high-performance non-bio-based fluorine-free skiing functional fabric and its preparation method in order to solve the problems of the prior art.
[0007] The present invention achieves the above objectives through the following technical solutions: As a first aspect of the present invention, a high-performance non-bio-based fluorine-free skiing functional fabric is provided, the fabric structure comprising a fluorine-free superhydrophobic nanofiber composite membrane and a bio-based nylon wear-resistant fabric hot-pressed onto both sides of the fluorine-free superhydrophobic nanofiber composite membrane via a hot-melt mesh as an intermediate adhesive medium. The fluorine-free superhydrophobic nanofiber composite membrane uses a PET / PDMS waterproof and breathable functional membrane as the main membrane, and then ferromagnetic-based fluorine-free superhydrophobic coating is arranged diagonally on both sides of the main membrane to form equally spaced parallel oblique arc-shaped membrane strips. The oblique directions of the arc-shaped membrane strips on both sides of the main membrane are opposite. The raw materials for preparing the ferromagnetic-based fluorine-free superhydrophobic coating include sponge iron powder that has been heat-treated with polyunsaturated fatty acids, divinylbenzene, azobisisobutyronitrile, hexagonal boron nitride, and deionized water.
[0008] As a further technical solution of the present invention, the PET / PDMS waterproof and breathable functional membrane is obtained by electrospinning and thermal curing of a PDMS / PET spinning solution; in the PDMS / PET spinning solution, the mass content of PDMS relative to PET is 20%-40%; The bio-based nylon abrasion-resistant fabric is woven with bio-based three-component functional yarn as warp and weft yarn. The bio-based three-component functional yarn is obtained by twisting bio-based nylon / ultra-high molecular weight polyethylene composite yarn as core yarn and PTT fiber or PBT fiber as outer yarn with a ply ratio of 1:2-4.
[0009] As a further technical solution of the present invention, the raw materials for preparing the bio-based nylon / ultra-high molecular weight polyethylene composite yarn include 88-95 parts by weight of bio-based nylon 66 chips, 4-10 parts by weight of ultra-high molecular weight polyethylene powder, and 1-2 parts by weight of linseed oil.
[0010] As a further technical solution of the present invention, the laying density of the arc-shaped membrane strip is not less than 100 strips per square meter of main membrane, and the arc of the arc-shaped membrane strip is 30°.
[0011] As a further technical solution of the present invention, the polyunsaturated fatty acids include linoleic acid or α-linolenic acid; The ratio of divinylbenzene, azobisisobutyronitrile, and sponge iron powder is 2:0.08-0.1:1-1.2. The ratio of hexagonal boron nitride to sponge iron powder is 0.05-0.1:1.
[0012] As a second aspect of the present invention, a method for preparing a high-performance bio-based fluorine-free skiing functional fabric as described in any one of the above claims is also provided, comprising the following steps: (1) Bio-based nylon abrasion-resistant fabric was obtained by weaving bio-based three-component functional yarns as warp and weft yarns; (2) Add the heat-treated sponge iron powder containing divinylbenzene, azobisisobutyronitrile and hexagonal boron nitride to a deionized aqueous solution to obtain a ferromagnetic-based fluorine-free superhydrophobic coating. (3) A PET / PDMS waterproof and breathable functional membrane is obtained by electrospinning and thermosetting the PDMS / PET spinning solution; (4) Using the PET / PDMS waterproof and breathable functional membrane prepared in step (3) as the main membrane, the ferromagnetic-based fluorine-free superhydrophobic coating prepared in step (2) is coated along the diagonal lines of both sides of the main membrane. Under the condition of applying an external magnetic field, thermally initiated polymerization is carried out to form equally spaced parallel oblique arc-shaped membrane strips. The oblique directions of the arc-shaped membrane strips on both sides of the main membrane are opposite. In this way, a fluorine-free superhydrophobic nanofiber composite membrane is prepared. (5) Place hot melt mesh on both sides of the fluorine-free superhydrophobic nanofiber composite membrane prepared in step (4), and composite the fluorine-free superhydrophobic nanofiber composite membrane between two layers of bio-based nylon wear-resistant fabric by hot pressing. After cooling at room temperature, the high-performance bio-based fluorine-free skiing functional fabric is obtained.
[0013] As a further technical solution of the present invention, in step (2), the sponge iron powder that has been heat-treated with polyunsaturated fatty acids is prepared by mixing the sponge iron powder and polyunsaturated fatty acids evenly, placing it in an oil bath at 150-160℃ for 3-5 hours, and then washing it with anhydrous ethanol 1-2 times.
[0014] As a further technical solution of the present invention, in step (3), the electrospinning process parameters are: spinning voltage of 22-25kV and solution injection speed of... The drum speed is 140-150 rpm, the receiving distance is 15-20 cm, the temperature is 20-25℃, and the relative humidity is 10%-15%.
[0015] As a further technical solution of the present invention, in step (4), the external magnetic field is applied in a spiral shape and moves back and forth perpendicularly to the arc-shaped membrane, covering the entire arc-shaped membrane area, repeating the movement trajectory 3 times, and the magnetic field strength is 0.5-1.0T.
[0016] As a further technical solution of the present invention, in step (4), the process parameters of hot pressing composite are: hot pressing temperature of 130-150°C, hot pressing pressure of 0.2-0.4MPa and hot pressing time of 15-30s.
[0017] The beneficial effects of this invention are as follows: (1) The ferromagnetic-based fluorine-free superhydrophobic coating of the present invention uses polyunsaturated fatty acid modified sponge iron powder combined with hexagonal boron nitride to construct a micro-nano binary rough hydrophobic structure to achieve a fluorine-free superhydrophobic effect. The PET / PDMS waterproof and breathable functional membrane is used as the main membrane. The ferromagnetic-based fluorine-free superhydrophobic coating is applied in a non-full-area coating method with equally spaced arc-shaped membrane strips. Unlike the traditional full-surface coating, it improves waterproofness through hydrophobic structure while preserving the pore structure of PET / PDMS nanofiber membrane to the greatest extent. It effectively solves the technical contradiction that conventional waterproof coatings are prone to clogging pores and significantly reducing moisture permeability and breathability. It can efficiently expel water vapor during exercise and improve wearing comfort.
[0018] (2) The present invention induces the oriented arrangement of ferromagnetic particles by reciprocating external magnetic field, avoiding the problem of inorganic particle agglomeration. The coating micro-nano structure is more uniform and regular, which not only improves the stability of hydrophobic structure, but also improves interface compatibility. Combined with the layer reinforcement effect of hexagonal boron nitride, it is beneficial to improve the bonding strength between fabrics, improve the durability of fabrics, and promote the long-term performance of fabric tear resistance and abrasion resistance. (3) The present invention uses bio-based nylon 66 compounded with ultra-high molecular weight polyethylene and linseed oil to prepare composite yarn, and combines it with PTT or PBT outer yarn to form a three-component functional yarn, giving the base fabric excellent mechanical properties and biodegradability. At the same time, the sandwich hot melt composite structure of fabric-composite film-fabric constructed has excellent wear resistance and strength performance of the fabric, which can be adapted to high-intensity outdoor sports scenarios such as ski suits. Detailed Implementation
[0019] The present application will now be described in further detail. It should be noted that the following specific embodiments are only used to further illustrate the present application and should not be construed as limiting the scope of protection of the present application. Those skilled in the art can make some non-essential improvements and adjustments to the present application based on the above content.
[0020] All materials and reagents not specified in this invention are commercially available, and all methods not specified can be performed using conventional methods.
[0021] Example 1
[0022] 1.1 Preparation of bio-based nylon / ultra-high molecular weight polyethylene composite yarn One-third of the formulation amount of bio-based nylon 66 chips (molecular weight 15,000-20,000) was melt-blended with the formulation amount of ultra-high molecular weight polyethylene powder (viscosity average molecular weight 250-400 million) and flaxseed oil. The blend was then directly fed into a screw extruder with an aspect ratio of 20:1 for melt extrusion and granulation to obtain masterbatch. The remaining formulation amount of bio-based nylon 66 chips and masterbatch were then fed into a screw extruder with an aspect ratio of 20:1 for melt extrusion, and side-blown cooling was used to obtain nascent filaments. The screw extruder's operating... The specific process parameters are as follows: the temperature of each section of the screw is 210°C for the feeding section, 230°C for the compression section, and 240°C for the metering section; the screw speed is 200 r / min; the length of the flow channel at the end of the screw extruder is 5 cm; the length-to-diameter ratio of the spinneret is 10:1; the obtained nascent filament is subjected to primary drafting at 110°C with a draft ratio of 2; and secondary drafting is performed at 130°C with a draft ratio of 2 to complete the drafting process, thus obtaining bio-based nylon / ultra-high molecular weight polyethylene composite yarn.
[0023] The raw materials for preparing bio-based nylon / ultra-high molecular weight polyethylene composite yarn include 88-95 parts by weight of bio-based nylon 66 chips, 4-10 parts by weight of ultra-high molecular weight polyethylene powder, and 1-2 parts by weight of linseed oil. In Example 1, the material formulation used for the bio-based nylon / ultra-high molecular weight polyethylene composite yarn is 91 parts by weight of bio-based nylon, 7 parts by weight of ultra-high molecular weight polyethylene powder, and 2 parts by weight of linseed oil.
[0024] 1.2 Preparation of Bio-based Three-component Functional Yarns The core yarn of the bio-based nylon / ultra-high molecular weight polyethylene composite yarn prepared in step 1.1 is used as the core yarn, and PTT fiber or PBT fiber is used as the outer yarn. The yarn is twisted together with a ply ratio of 1:2-4 (the twisting process is well known to those skilled in the art, and each group is prepared using the same process parameters, which will not be described in detail). In Example 1, PTT fiber is selected as the outer yarn and the ply ratio is 4.
[0025] 1.3 Preparation of Bio-based Nylon Abrasion-resistant Fabric Bio-based three-component functional yarns are used as warp and weft yarns to obtain bio-based nylon abrasion-resistant fabric through weaving. In this embodiment, the fixed weaving parameters are that the warp yarn weaving density is 65 ends / cm, the weft yarn weaving density is 55 ends / cm, and the fabric weave is plain weave.
[0026] Example 2
[0027] 2.1 Preparation of PET / PDMS spinning solution The steps are as follows: LiCl particles are dissolved in a mixed solvent of TFA and DCM (6:1, w / w), with a LiCl concentration of 0.01 wt%. Different amounts of PDMS (molecular weight of 50,000-100,000) are dissolved in the above solution, and the mixture is stirred at room temperature for 2 hours to obtain a clear PDMS solution. PET particles are dissolved in the above clear PDMS solution, and the mixture is stirred at room temperature for 12 hours to obtain a PET / PDMS spinning solution. The total concentration of the PET and PDMS solutions is maintained at 12 wt%. The mass content of PDMS relative to PET is 20%-40%. In this Example 2, the mass content of PDMS relative to PET is set to 30%.
[0028] 2.2 Preparation of PET / PDMS Waterproof and Breathable Functional Membrane The steps are as follows: The PET / PDMS spinning solution is loaded into a 10ml syringe to expel air and bubbles. PET / PDMS nanofiber membranes are then prepared using an electrospinning apparatus. The electrospinning process parameters are: spinning voltage of 22-25kV, and solution injection speed of… The drum rotation speed is 140-150 rpm, the receiving distance is 15-20 cm, the temperature is 20-25℃, and the relative humidity is 10%-15%. In this embodiment 2, the spinning voltage is set to 22 kV, and the solution injection speed is... The roller speed is 140 rpm, and the receiving distance is 20 cm. In addition, the relative humidity during the spinning process is controlled at 25℃ and 10%RH, respectively.
[0029] The nanofiber membrane removed from the roller surface was subjected to heat curing treatment. The prepared nanofiber membrane was fixed around the edges with high-temperature resistant tape, placed in an oven and heated at 120°C for 1 hour to set the shape, while removing residual solvent. By controlling the spinning time under the same spinning conditions, the thickness of the prepared PET / PDMS waterproof and breathable functional membrane was controlled to 60±5μm.
[0030] Example 3
[0031] 3.1 Preparation of Ferromagnetic-based Fluorine-free Superhydrophobic Coatings The steps are as follows: Sponge iron powder (20-40 μm) and polyunsaturated acid are mixed evenly and then treated in an oil bath at 150-160℃ for 3-5 hours, followed by washing with anhydrous ethanol 1-2 times. In Example 3, the temperature was 160℃, the treatment time was 3 hours, and the mixture was washed twice with anhydrous ethanol. The treated sponge iron powder was added to a deionized aqueous solution containing divinylbenzene, azobisisobutyronitrile, and hexagonal boron nitride, and placed in a water bath constant-temperature shaker for 24 hours to obtain a ferromagnetic-based fluorine-free superhydrophobic coating. The formulation of the ferromagnetic-based fluorine-free superhydrophobic coating is shown in Table 1.
[0032] Table 1. Formulation of Ferromagnetic-based Fluorine-free Superhydrophobic Coatings
[0033] In addition, groups T-4, T-5, T-6, T-7, and T-8 were set up as control groups; among them, The difference between group T-4 and group T-3 is that hexagonal boron nitride is not added; The difference between the T-5 group and the T-3 group is that silicon nitride is used instead of hexagonal boron nitride; The difference between group T-6 and group T-3 is that the sponge iron powder does not undergo linoleic acid heat treatment. The difference between group T-7 and group T-3 is that the sponge iron powder is heat-treated with α-linolenic acid. The difference between group T-8 and group T-3 is that group T-8 uses zinc powder of the same specifications instead of sponge iron powder.
[0034] 3.2 Preparation of Fluorine-Free Superhydrophobic Nanofiber Composite Membranes Using the PET / PDMS waterproof and breathable functional membrane prepared in Example 2 as the main membrane, the above-mentioned coating was coated along the diagonal of both sides of the main membrane. Under the condition of applying an external magnetic field, thermally initiated polymerization was carried out to form equally spaced parallel oblique arc-shaped membrane strips. The density was 100 strips per square meter of main membrane, the curvature of the arc-shaped membrane strips was 30°, and the oblique direction of the arc-shaped membrane strips on both sides of the main membrane was opposite. In this way, a fluorine-free superhydrophobic nanofiber composite membrane was prepared. The thermally initiated polymerization reaction time was 6 hours, the reaction temperature was 85°, and the external magnetic field was applied in a spiral shape and moved back and forth perpendicularly to the arc-shaped membrane strips, covering the entire arc-shaped membrane strip area. The movement trajectory was repeated 3 times, and the magnetic field strength was 0.5-1.0T. In this example, it was set to 1.0T.
[0035] Following the above method, the fluorine-free superhydrophobic nanofiber composite membranes prepared using different coatings T-1 to T-8 are denoted as TY-1 to TY-8.
[0036] 3.3 Performance Characterization (1) Surface wettability test The surface wettability of the sample, i.e., the water contact angle (WCA), was measured using a contact angle meter with a liquid droplet size of 3 μL. Five parallel tests were performed, and the average value was taken.
[0037] (2) Mechanical property testing The mechanical properties of the nanocomposite membrane were characterized using a tensile strength tester. All samples to be tested were cut into strips 1 cm wide and 5 cm long, and the tensile speed was fixed at 10 mm / min. Five parallel tests were performed, and the average value was taken.
[0038] (3) Waterproof performance test The waterproof performance of the samples was characterized by water pressure resistance. The water pressure resistance of the samples was measured using a water permeability tester (YG812F). Test parameters: pressure increase rate. The sample is laid flat in the instrument's testing area, and a plain-weave fabric is placed over the surface of the composite membrane to prevent excessive deformation during testing. During the test, the inner side of the composite membrane is continuously subjected to a steadily increasing water pressure. The pressure is applied until three drops of water appear on the front, at which point the pressure value (kPa) displayed is the water pressure resistance value of the test sample.
[0039] (4) Moisture permeability test The moisture permeability of the samples was characterized by a percentage (%). The moisture permeability was measured using a water vapor transmission rate tester. Test parameters: positive cup method; temperature and humidity parameters within the instrument chamber were 35℃ and 90% respectively. Specific test procedures: 15g of deionized water was weighed and placed in the moisture permeability measuring cup. The composite membrane to be tested was cut into a suitable circle and tightly fixed at the mouth of the cup. The cup was placed inside the moisture permeability instrument with the mouth facing upwards. The moisture permeability (%) of the sample was calculated as follows: ; In the formula, and These represent the mass of the measuring cup before and after the test per unit time, respectively. This represents the effective test area. Five parallel tests were performed, and the average value was taken.
[0040] (5) Air permeability test The air permeability of the samples was characterized using a fully automated fabric air permeability meter (YG461E-Ⅲ). The test area was 20 cm². 2 The test pressure was 100 Pa. Five parallel tests were performed, and the average value was taken.
[0041] The performance characterization results of composite membranes TY-1 to TY-8 are summarized in Table 2. In addition, the same performance tests were performed on the PET / PDMS waterproof and breathable functional membrane (denoted as TY-9) prepared in Example 2, and the results are also summarized in Table 2.
[0042] Table 2. Results Statistics Table
[0043] As can be seen from Table 2, comparing composite membranes TY-1 to TY-3: with the increase of hexagonal boron nitride content, the micro-nano rough structure on the surface of the composite membrane is more perfect, which gradually improves the contact angle, water pressure resistance and tensile strength of the composite membrane; at the same time, the increase of the proportion of hexagonal boron nitride content enhances the rigidity of the composite membrane, while the elongation at break and air permeability and moisture permeability decrease slightly. Composite membrane TY-4, without the addition of hexagonal boron nitride, relies solely on sponge iron powder to construct a micron-level rough structure, failing to form an efficient binary roughness. Its contact angle does not reach superhydrophobic levels, and all its properties are weaker than composite membrane TY-3. Composite membrane TY-5 uses silicon nitride instead of hexagonal boron nitride. Silicon nitride's intrinsic hydrophobicity is weaker than that of hexagonal boron nitride, and its layer reinforcement effect is poor, resulting in lower contact angles and mechanical properties compared to composite membrane TY-3. Composite membrane TY-6 uses unmodified sponge iron powder, increasing the overall surface energy of the coating and significantly decreasing the contact angle. It also exhibits poor interfacial compatibility, with water pressure resistance lower than TY-9. Composite membrane TY-7 uses sponge iron powder modified with α-linolenic acid, which, like linoleic acid, is a long-chain unsaturated fatty acid, resulting in a similar hydrophobic modification effect, but its performance is slightly lower than TY-3. Composite membrane TY-8 uses zinc powder instead of sponge iron powder. Since zinc powder is non-ferromagnetic, it cannot be oriented under a magnetic field, leading to uneven coating dispersion and a loose micro-nano rough structure, resulting in inferior performance compared to composite membrane TY-3.
[0044] To investigate the effect of preparation method on membrane performance, the following control group was further set up: Control group 1: Using the PET / PDMS waterproof and breathable functional membrane prepared in Example 2 as the main membrane, the above-mentioned coating TY-3 was coated along the diagonal of both sides of the main membrane. Thermally initiated polymerization was carried out without the application of an external magnetic field to form equally spaced parallel oblique arc-shaped membrane strips. The density of the strips was 100 strips per square meter of main membrane, the curvature of the arc-shaped membrane strips was 30°, and the oblique direction of the arc-shaped membrane strips on both sides of the main membrane was opposite. In this way, a fluorine-free superhydrophobic nanofiber composite membrane was prepared. The thermally initiated polymerization reaction time was 6 hours and the reaction temperature was 85°C.
[0045] Control group 2: Using the PET / PDMS waterproof and breathable membrane prepared in Example 2 as the main membrane, the aforementioned coating TY-3 was coated along the diagonal lines of both sides of the main membrane. Thermally initiated polymerization was then carried out under an applied external magnetic field to form equally spaced, parallel, obliquely oriented arc-shaped membrane strips. The density was 100 strips per square meter of the main membrane, with an arc angle of 30°. The oblique direction of the arc-shaped membrane strips on both sides of the main membrane was the same. This method yielded a fluorine-free superhydrophobic nanofiber composite membrane. The thermally initiated polymerization reaction time was 6 hours, and the reaction temperature was 85°C. The external magnetic field was applied in a spiral pattern, reciprocating perpendicularly to the arc-shaped membrane strips, covering the entire arc-shaped membrane strip area. This movement trajectory was repeated three times, and the magnetic field strength was 1.0T.
[0046] Control group 3: Using the PET / PDMS waterproof and breathable membrane prepared in Example 2 as the main membrane, the aforementioned coating TY-3 was coated along the diagonal lines of both sides of the main membrane. Under an applied external magnetic field, the membrane was left at room temperature for 6 hours to form equally spaced, parallel, obliquely oriented arc-shaped membrane strips. The density of these strips was 100 strips per square meter of the main membrane, with an arc angle of 30°. The oblique directions of the arc-shaped membrane strips on both sides of the main membrane were opposite. This method yielded a fluorine-free superhydrophobic nanofiber composite membrane. The external magnetic field was applied in a spiral motion, intersecting the arc-shaped membrane strips perpendicularly, covering the entire arc-shaped membrane strip area. This movement trajectory was repeated three times, with a magnetic field strength of 1.0T.
[0047] Control group 4: Using the PET / PDMS waterproof and breathable functional membrane prepared in Example 2 as the main membrane, the above-mentioned coating TY-3 was coated along the diagonal lines of both sides of the main membrane. Under the condition of no external magnetic field, it was placed at room temperature for 6 hours to form equally spaced parallel oblique arc-shaped membrane strips. The density of the strips was 100 strips per square meter of the main membrane, the curvature of the arc-shaped membrane strips was 30°, and the oblique direction of the arc-shaped membrane strips on both sides of the main membrane was opposite. In this way, a fluorine-free superhydrophobic nanofiber composite membrane was prepared.
[0048] Control group 5: Using the PET / PDMS waterproof and breathable functional membrane prepared in Example 2 as the main membrane, the above-mentioned coating TY-3 was coated along the diagonal lines of both sides of the main membrane. Under the condition of applying an external magnetic field, thermally initiated polymerization was carried out to form equally spaced parallel oblique arc-shaped membrane strips. The density of the strips was 100 strips per square meter of the main membrane, the curvature of the arc-shaped membrane strips was 30°, and the oblique direction of the arc-shaped membrane strips on both sides of the main membrane was opposite. In this way, a fluorine-free superhydrophobic nanofiber composite membrane was prepared. The thermally initiated polymerization reaction time was 6 hours, the reaction temperature was 85°C, the external magnetic field was applied in a fixed manner, covering the entire arc-shaped membrane strip area, the application time was the same as that of the composite membrane, and the magnetic field strength was 1.0T.
[0049] Control group 6: Using the PET / PDMS waterproof and breathable functional membrane prepared in Example 2 as the main membrane, the above-mentioned coating TY-3 was coated along the diagonal of both sides of the main membrane. Under the condition of applying an external magnetic field, thermally initiated polymerization was carried out to form equally spaced parallel oblique arc-shaped membrane strips. The density was 100 strips per square meter of main membrane. The curvature of the arc-shaped membrane strips was 0° (straight membrane strips). The oblique directions of the arc-shaped membrane strips on both sides of the main membrane were opposite. In this way, a fluorine-free superhydrophobic nanofiber composite membrane was prepared. The thermally initiated polymerization reaction time was 6 hours, the reaction temperature was 85°C, and the external magnetic field was applied in a spiral shape and moved back and forth perpendicularly to the arc-shaped membrane strips, covering the entire arc-shaped membrane strip area. The movement trajectory was repeated 3 times, and the magnetic field strength was 1.0T.
[0050] The composite membranes prepared from control groups 1 to 6 are designated as DMY-1 to DMY-6. Performance tests were performed on composite membranes DMY-1 to DMY-6 as shown in 3.3, and the test results are summarized in Table 3.
[0051] Table 3. Results Statistics Table
[0052] As shown in Table 3, without the application of an external magnetic field, the composite membrane DMY-1 exhibits disordered distribution of ferromagnetic particles, resulting in a rough and uneven coating structure, and a significant decrease in contact angle and water pressure resistance. Particle agglomeration leads to stress concentration and a decline in mechanical properties. The composite membrane DMY-2 has two curved membrane strips on both sides of the main membrane with the same oblique direction, so the contact angle is less affected. The same oblique direction weakens the labyrinth effect of the composite membrane, shortens the water seepage path, significantly reduces water pressure resistance, and the stress distribution of the membrane is asymmetrical, resulting in reduced mechanical properties. The composite membrane DMY-3 has no thermally initiated polymerization, and the divinylbenzene is not cross-linked and cured, so the coating is loose and has no strength, and the improvement in contact angle and water pressure resistance is limited. However, the coating porosity is high, and the air and moisture permeability is close to that of TY-3. The composite membrane DMY-4 has no external magnetic field treatment and no thermally initiated polymerization, so the particles are disordered and not polymerized, resulting in reduced mechanical properties. The composite membrane DMY-5 has an external magnetic field applied at a fixed position, and the particles are only oriented in a single direction, resulting in poor distribution uniformity. The overall performance is between that of TY-3 and DMY-1. The composite membrane DMY-6 has a straight membrane strip with weaker flow guidance and labyrinth effect than the curved one, and the water pressure resistance is reduced. However, the straight structure blocks the pores less, and the air and moisture permeability is slightly higher than that of TY-3.
[0053] Example 4: Preparation of high-performance bio-based fluorine-free skiing functional fabric Hot-melt mesh films were placed on both sides of composite films TY-3 and DMY-1 to DMY-6 in sequence. The composite films were then bonded between the two layers of bio-based nylon abrasion-resistant fabric prepared in Example 1 by hot-pressing. After cooling at room temperature, the high-performance bio-based fluorine-free skiing functional fabric was obtained. The hot-pressing temperature was 130-150°C, the hot-pressing pressure was 0.2-0.4 MPa, and the hot-pressing time was 15-30 s. In this example, the hot-pressing temperature was set to 130°C, the hot-pressing pressure to 0.4 MPa, and the hot-pressing time to 30 s.
[0054] The prepared fabrics were designated as fabrics Y-1 to Y-7, and the following mechanical properties were tested on the fabric samples: (1) Breaking strength test: Referring to GB / T3923.1-2013, 20cm×5cm strips from the same batch as the breaking elongation test were used. Under the same standard environment and electronic fabric strength tester parameters (clamping distance 10cm, stretching speed 100mm / min), the warp and weft samples were stretched. The maximum tensile force value when the sample broke was recorded, which is the breaking strength (N). Five parallel tests were performed and the average value was taken.
[0055] (2) Abrasion resistance test: The friction loss of the sample was determined according to the standard GB / T21196.3-2007 "Textiles Martindale Method for the determination of abrasion resistance of fabrics Part 3: Determination of mass loss". The friction loss is the mass loss after 2000 friction cycles. The greater the friction loss, the more severe the wear and the worse the abrasion resistance of the fabric. Five parallel tests were conducted and the average value was taken.
[0056] (3) Peel strength test: The peel strength test was conducted in accordance with the standard FZ / T01085- "Test Method for Peel Strength of Hot Melt Bonded Interlining". In this test, an electronic single fiber tensile tester was used to test the peel strength of the fabric. The sample size was 15mm×100mm, the spacing length was 10mm, and the tensile speed was 100mm / min. Each sample was tested 5 times according to the standard, and the average value of the 5 parallel tests was taken.
[0057] Furthermore, the fabric samples were tested for hydrostatic pressure resistance and water repellency. (4) Hydrostatic pressure resistance test: The fabric was subjected to a hydrostatic pressure test according to GB / T4744-2013. The test method was as follows: the test water on the clamping surface was wiped clean, the sample was clamped, and the front of the sample was in contact with the water. The water pressure was continuously increased at a rate of 60 cmH2O / min, and the water seepage phenomenon was observed. During the pressure increase, when the third water droplet just appeared on the sample, the pressure increase was stopped, and the hydrostatic pressure value at this time was recorded. Five parallel tests were performed and the average value was taken.
[0058] (5) Water repellency rating test: In a standard laboratory, distilled water is sprayed onto the sample through a funnel, and the sample is rated according to the waterproof standard (European standard ISO4920).
[0059] In addition, for comparison: the fabric that was composited by hot-pressing between the two layers of bio-based nylon abrasion-resistant fabric prepared in Example 1 with a hot-melt mesh film was denoted as fabric Y-8. The hot-pressing composite process parameters were the same as those of fabrics Y-1 to Y-7. A hot melt mesh film was placed on both sides of the PET / PDMS waterproof and breathable functional film prepared in Example 2. The functional film was then laminated to the fabric between the two layers of bio-based nylon wear-resistant fabric prepared in Example 1 by hot pressing. This fabric is denoted as fabric Y-9. The hot pressing process parameters are the same as those for fabrics Y-1 to Y-7.
[0060] The above performance tests were also performed on fabrics Y-8 to Y-9, and the test results of fabrics Y-1 to Y-9 are summarized in Table 4.
[0061] Table 4. Results Statistics Table
[0062] As shown in Table 4, the functional fabric obtained by laminating the composite membrane TY-3 between two layers of bio-based nylon abrasion-resistant fabric using a hot melt web as the adhesive medium has excellent tear resistance, abrasion resistance, and waterproof performance. Furthermore, the high peel strength between the composite fabrics is beneficial to improving the overall durability of the fabric and promoting the long-term performance of the fabric's tear resistance and abrasion resistance.
[0063] Fabric Y8 consists of only two layers of bio-based nylon fabric heat-pressed together without a functional interlayer. It has the lowest tensile strength, the greatest wear mass loss, a hydrostatic pressure resistance of only 5480 mmH2O, and a water repellency rating of only level 3, which cannot meet the waterproof requirements of ski fabrics. Fabric Y9 is composited with a raw PET / PDMS waterproof and breathable membrane without a superhydrophobic coating. Its performance is better than fabric Y8, but far lower than fabric Y1. This proves that a ferromagnetic-based fluorine-free superhydrophobic coating is the key to achieving high water pressure resistance and high water repellency in fabrics. The overall performance of fabric Y1 is better than that of fabric Y-8, which is traditionally composited with a hot-melt web film, and it can be well applied to outdoor sports equipment fabrics such as ski suits.
[0064] The above-described embodiments are merely examples of several implementations of the present invention, and their descriptions are relatively specific and detailed. However, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.
Claims
1. A high-performance bio-based fluorine-free skiing functional fabric, characterized in that, The fabric structure includes a fluorine-free superhydrophobic nanofiber composite membrane and a bio-based nylon wear-resistant fabric that is hot-pressed onto both sides of the fluorine-free superhydrophobic nanofiber composite membrane using a hot-melt mesh as an intermediate adhesive medium. The fluorine-free superhydrophobic nanofiber composite membrane uses a PET / PDMS waterproof and breathable functional membrane as the main membrane, and then ferromagnetic-based fluorine-free superhydrophobic coating is arranged diagonally on both sides of the main membrane to form equally spaced parallel oblique arc-shaped membrane strips. The oblique directions of the arc-shaped membrane strips on both sides of the main membrane are opposite. The raw materials for preparing the ferromagnetic-based fluorine-free superhydrophobic coating include sponge iron powder that has been heat-treated with polyunsaturated fatty acids, divinylbenzene, azobisisobutyronitrile, hexagonal boron nitride, and deionized water.
2. The high-performance bio-based fluorine-free skiing functional fabric according to claim 1, characterized in that, The PET / PDMS waterproof and breathable functional membrane is obtained by electrospinning and thermal curing of PDMS / PET spinning solution; in the PDMS / PET spinning solution, the mass content of PDMS relative to PET is 20%-40%.
3. The high-performance bio-based fluorine-free skiing functional fabric according to claim 1, characterized in that, The bio-based nylon abrasion-resistant fabric is woven with bio-based three-component functional yarn as warp and weft yarn. The bio-based three-component functional yarn is obtained by twisting bio-based nylon / ultra-high molecular weight polyethylene composite yarn as core yarn and PTT fiber or PBT fiber as outer yarn with a ply ratio of 1:2-4. The raw materials for preparing the bio-based nylon / ultra-high molecular weight polyethylene composite yarn include 88-95 parts by weight of bio-based nylon 66 chips, 4-10 parts by weight of ultra-high molecular weight polyethylene powder, and 1-2 parts by weight of linseed oil.
4. The high-performance bio-based fluorine-free skiing functional fabric according to claim 1, characterized in that, The density of the arc-shaped membrane strips is no less than 100 strips per square meter of the main membrane, and the arc of the arc-shaped membrane strips is 30°.
5. The high-performance bio-based fluorine-free skiing functional fabric according to claim 1, characterized in that, The polyunsaturated fatty acids include linoleic acid or alpha-linolenic acid; The ratio of divinylbenzene, azobisisobutyronitrile, and sponge iron powder is 2:0.08-0.1:1-1.
2. The ratio of hexagonal boron nitride to sponge iron powder is 0.05-0.1:
1.
6. A method for preparing a high-performance bio-based fluorine-free skiing functional fabric as described in any one of claims 1-5, characterized in that, Includes the following steps: (1) Bio-based nylon abrasion-resistant fabric was obtained by weaving bio-based three-component functional yarns as warp and weft yarns; (2) Add the heat-treated sponge iron powder containing divinylbenzene, azobisisobutyronitrile and hexagonal boron nitride to a deionized aqueous solution to obtain a ferromagnetic-based fluorine-free superhydrophobic coating. (3) A PET / PDMS waterproof and breathable functional membrane is obtained by electrospinning and thermosetting the PDMS / PET spinning solution; (4) Using the PET / PDMS waterproof and breathable functional membrane prepared in step (3) as the main membrane, the ferromagnetic-based fluorine-free superhydrophobic coating prepared in step (2) is coated along the diagonal lines of both sides of the main membrane. Under the condition of applying an external magnetic field, thermally initiated polymerization is carried out to form equally spaced parallel oblique arc-shaped membrane strips. The oblique directions of the arc-shaped membrane strips on both sides of the main membrane are opposite. In this way, a fluorine-free superhydrophobic nanofiber composite membrane is prepared. (5) Place hot melt mesh on both sides of the fluorine-free superhydrophobic nanofiber composite membrane prepared in step (4), and composite the fluorine-free superhydrophobic nanofiber composite membrane between two layers of bio-based nylon wear-resistant fabric by hot pressing. After cooling at room temperature, the high-performance bio-based fluorine-free skiing functional fabric is obtained.
7. The method for preparing high-performance bio-based fluorine-free skiing functional fabric according to claim 6, characterized in that, In step (2), the sponge iron powder that has been heat-treated with polyunsaturated fatty acids is prepared by mixing the sponge iron powder and polyunsaturated fatty acids evenly, placing it in an oil bath at 150-160℃ for 3-5 hours, and then washing it with anhydrous ethanol 1-2 times.
8. The method for preparing high-performance bio-based fluorine-free skiing functional fabric according to claim 6, characterized in that, In step (3), the electrospinning process parameters are: spinning voltage of 22-25kV and solution injection speed of... The drum speed is 140-150 rpm, the receiving distance is 15-20 cm, the temperature is 20-25℃, and the relative humidity is 10%-15%.
9. The method for preparing high-performance bio-based fluorine-free skiing functional fabric according to claim 6, characterized in that, In step (4), the external magnetic field is applied in a spiral shape and moves back and forth perpendicularly to the arc-shaped membrane, covering the entire arc-shaped membrane area, repeating the movement trajectory 3 times, with a magnetic field strength of 0.5-1.0T.
10. The method for preparing the high-performance bio-based fluorine-free skiing functional fabric according to claim 6, characterized in that, In step (4), the hot-pressing composite process parameters are: hot-pressing temperature of 130-150°C, hot-pressing pressure of 0.2-0.4 MPa, and hot-pressing time of 15-30 s.